Integrated Marketing: A Powerful Strategy for Increasing Brand Awareness - Dewi Indriani Jusuf (International Publisher, 2024)
In an increasingly competitive business era, it is important for companies to develop effective marketing strategies to expand coverage and increase brand awareness among consumers. This research aims to explore and analyze the effectiveness of implementing integrated marketing strategies as a means of increasing brand awareness in the current competitive market context. The research method used is a qualitative approach with in-depth interviews with several marketing professionals and analysis of case studies from several companies that have succeeded in implementing integrated marketing strategies effectively. The research results show that implementing an integrated marketing strategy effectively strengthens brand awareness, expands market reach, and strengthens consumer engagement. By focusing on message consistency across various communication channels, this strategy helps companies reach a wider target audience, build strong relationships with consumers, and establish a strong brand image. In addition, integrated marketing strategies are also proven to optimize the use of resources by avoiding the need for expensive content duplication, strengthening efficiency in marketing campaign management. Thus, the results of this research emphasize the importance of an integrated marketing strategy as a solid foundation in winning an increasingly competitive market and ensuring sustainable growth in the long term.